The Political Economy of Teacher Management in Decentralized Indonesia - Rosser, Andrew; Fahmi, Mohamad (World Bank, Washington, DC, 2017)
Indonesia faces serious challenges in the number, cost, quality, and distribution of teachers. This paper examines the role of political economy factors in producing these challenges and shaping efforts to resolve them. It argues that the challenges have their origins in the way in which political and bureaucratic elites have for decades used the school system to accumulate resources, distribute patronage, mobilize political support, and exercise political control. This orientation has meant that teacher numbers, quality, and distribution have been managed to maximize flows of rents and votes from schools to the elite, lubricate patronage and political networks, and ensure that elites maintain political control rather than maximize educational performance and equity. The fall of the New Order, the authoritarian and centralized regime that ruled Indonesia from 1965 to 1998, led to efforts to change this situation, but these have had little impact so far. The paper concludes by assessing what can be done by proponents of teacher management reform in this context to promote better outcomes.